Kemandirian Petani dalam Pengembangan Usahatani Alpukat - Shubhi, Naufal Rastra; Wibowo, Agung; Suminah, Suminah (Jurnal Sosial Ekonomi Pertanian, 2024)
Avocados have good benefits for the health of the human body, maintain heart health, contain vitamin C, vitamin B-6, folate, vitamin E, vitamin K, and vitamin A, and help lower bad cholesterol levels. This condition increases the interest of avocado consumers in the market sector. This condition requires farmers to cultivate avocados independently to optimize avocado productivity. Farmer independence is associated with the decision to manage crops and the types of commodities that are cultivated to survive in the midst of the situation and conditions of the small-scale agricultural sector to be sustainable in the future. This study aims to 1). Examine the independence of farmers in avocado cultivation and 2). Knowing the factors that affect the independence of farmers in avocado cultivation. The methods used in this study are quantitative and data collection using questionnaires. The location determination in this study was carried out (purposive) in Sanggang Village. Sampling was conducted using the random sampling method and 35 farmers responded. The analysis uses a multiple linear regression test with the help of IBM SPSS Statistics 25. Based on the test results by comparing the sig value with a significance level of (0.05), it was found that: The results of the multiple linear regression analysis showed that the non-formal education variable had a Sig. (0.033) value, the social environment had a Sig. (0.002) value and the land area had a Sig. (0.006), which means that the variable affected the farmer's independence while the farming experience variable had a Sig. (0.290) value affecting the independence of farmers. The value of R Square (R2) in this study is 0.721.